2011
DOI: 10.1111/j.1365-2656.2011.01872.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression and costs between maternally and paternally derived immune priming for offspring in an insect

Abstract: Summary1. When parasitized, both vertebrates and invertebrates can enhance the immune defence of their offspring, although this transfer of immunity is achieved by different mechanisms. In some insects, immune-challenged males can also initiate trans-generational immune priming (TGIP), but its expressions appear qualitatively different from the one induced by females similarly challenged. 2. The existence of male TGIP challenges the traditional view of the parental investment theory, which predicts that female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
156
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(169 citation statements)
references
References 31 publications
8
156
5
Order By: Relevance
“…This transgenerational immune priming (TGIP) increases immune activity in eggs laid by immune challenged parents, even in the absence of egg infection (Little and Kraaijeveld, 2004). Priming prepares the eggs for the impending danger by triggering differential expression of immune-related genes in eggs and/or via the direct transmission of immune factors into eggs (Freitak et al, 2014(Freitak et al, , 2009Knorr et al, 2015;Trauer-Kizilelma and Hilker, 2015;Trauer and Hilker, 2013;Zanchi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This transgenerational immune priming (TGIP) increases immune activity in eggs laid by immune challenged parents, even in the absence of egg infection (Little and Kraaijeveld, 2004). Priming prepares the eggs for the impending danger by triggering differential expression of immune-related genes in eggs and/or via the direct transmission of immune factors into eggs (Freitak et al, 2014(Freitak et al, , 2009Knorr et al, 2015;Trauer-Kizilelma and Hilker, 2015;Trauer and Hilker, 2013;Zanchi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…We experimentally address the extent to which interactions between maternal and paternal age, and maternal, paternal and offspring immune activation, shape early-life reproductive success. By exploring the interaction between parental immune status and offspring immune status, we are also able to explore the potential for parental transfer of innate immunity factors, a controversial premise with emerging experimental support [9,[33][34][35][36]42,43].…”
Section: Introductionmentioning
confidence: 99%
“…In this adaptive branch, studies have demonstrated age-related deterioration caused by alterations of T cells and a decreasing abundance of naive B cells [25], as well as general transgenerational effects in which mothers transfer immune factors to offspring through the placenta, colostrum or breast milk [3,28]. Less is known about the capacity for age-dependent or transgenerational effects in the innate branch of the immune system common to all metazoans [9,[25][26][27][29][30][31]. Historically, it was assumed that the innate immune system only provided immediate, non-specific immune responses, lacking in immune memory [32] and transgenerational transfer of immune factors [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas immune priming increases host resistance to pathogens during second and subsequent encounters, transgenerational immune priming allows the offspring of the host to benefit from the same resistance even on their first encounter with the pathogen (Figure 3) [129][130][131][132][133]. However, individual immune priming by systemic injection would prove difficult in mass-reared insects due to their relatively small size and great number.…”
Section: Immune Priming and Transgenerational Immune Primingmentioning
confidence: 99%